Theories on the Pathogenesis of Endometriosis - Sourial, Samer; Tempest, Nicola; Hapangama, Dharani K. (International Journal of Reproductive Medicine, 2014)
Endometriosis is a common, chronic inflammatory disease defined by the presence of extrauterine endometrial tissue. The aetiology of endometriosis is complex and multifactorial, where several not fully confirmed theories describe its pathogenesis. This review examines existing theories on the initiation and propagation of different types of endometriotic lesions, as well as critically appraises the myriad of biologically relevant evidence that support or oppose each of the proposed theories. The current literature suggests that stem cells, dysfunctional immune response, genetic predisposition, and aberrant peritoneal environment may all be involved in the establishment and propagation of endometriotic lesions. An orchestrated scientific and clinical effort is needed to consider all factors involved in the pathogenesis of this multifaceted disease and to propose novel therapeutic targets to reach effective treatments for this distressing condition.